Outcomes in patients with aggressive or refractory disease from REVEL: a randomized phase III study of docetaxel with ramucirumab or placebo for second-line treatment of stage IV non-small-cell lung cancer - Reck, Martin; Thomas, Michael (Lung cancer, 2017)
Objectives The REVEL study demonstrated improved efficacy for patients with advanced non-small cell lung cancer treated with ramucirumab plus docetaxel, independent of histology. This exploratory analysis characterized the treatment effect in REVEL patients who were refractory to prior first-line treatment. Materials and methods Refractory patients had a best response of progressive disease to first-line treatment. Endpoints included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), quality of life (QoL), and safety. Kaplan-Meier and Cox proportional hazards regression were performed for OS and PFS, and Cochran-Mantel-Haenszel test was used for response. QoL was assessed with the Lung Cancer Symptom Scale. Sensitivity analyses were performed on subgroups of the intent-to-treat population with limited time on first-line therapy. Results Of 1253 randomized patients in REVEL, 360 (29%) were refractory to first-line treatment. Baseline characteristics were largely balanced between treatment arms. In the control arm, median OS for refractory patients was 6.3 versus 10.3 months for patients not meeting this criterion, demonstrating the poor prognosis of refractory patients. Median OS (8.3 vs. 6.3 months; HR, 0.86; 95% CI, 0.68-1.08), median PFS (4.0 vs. 2.5 months; HR, 0.71; 95% CI, 0.57-0.88), and ORR (22.5% vs. 12.6%) were improved in refractory patients treated with ramucirumab compared to placebo, without new safety concerns or further deteriorating patient QoL. Conclusions The effect of ramucirumab in refractory patients is similar to that in the intent-to-treat population. The benefit/risk profile for refractory patients suggests that ramucirumab plus docetaxel is an appropriate treatment option even in this difficult-to-treat population.
Gesehen am 24.04.2018